CpxR promotes the carbapenem antibiotic resistance of Klebsiella pneumoniae by directly regulating the expression and the dissemination of blaKPC on the IncFII conjugative plasmid - Zhiyuan Liu; Jiahao Guan; Zhaoyan Chen; Cui Tai; Zixin Deng; Yanjie Chao; Hong-Yu Ou (Emerging Microbes and Infections, 2023)
Klebsiella pneumoniae is an important human pathogen known for its resistance to carbapenem antibiotics, especially the increasing carbapenem-resistant hypervirulent variants. The carbapenem resistance is mainly caused by the carbapenemase gene blaKPC which was commonly found on the IncFII transferable plasmids in K. pneumoniae ST11 isolates in regions of China. However, the mechanisms of the plasmid-carrying blaKPC regulation by the host strain are not clear. To investigate the chromosome-encoded two-component system (TCS) that regulates the carbapenem resistance of K. pneumoniae caused by blaKPC, twenty-four TCSs of a carbapenem-resistant classical K. pneumoniae ST11 clinical isolate were knocked out. The deletion mutation of the TCS regulator cpxR exhibited increased sensitivity to carbapenem, which could be restored by complementation with cpxR in trans. Electrophoretic mobility shift, isothermal titration calorimetry and DNase I footprinting results revealed that CpxR directly bound to the promoter DNA of blaKPC and the binding was abolished by disrupting the DNA-binding domain in CpxR. The subsequent in vivo assays using the lacZ reporter system and qPCR showed that CpxR upregulates the transcription of blaKPC. Notably, CpxR was also found to activate the transfer of the blaKPC-carrying IncFII plasmid between the hypervirulent K. pneumoniae and E. coli isolates, in which CpxR promoted the transcription of the tra operon via binding to its promoter region. These results provide an important insight into the regulation of the host factor CpxR in the plasmid-carrying carbapenemase gene in the classical and hypervirulent K. pneumoniae.